2009
DOI: 10.1038/cdd.2009.49
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide is the major reactive oxygen species regulating autophagy

Abstract: Autophagy is involved in human diseases and is regulated by reactive oxygen species (ROS) including superoxide (O 2 KÀ ) and hydrogen peroxide (H 2 O 2 ). However, the relative functions of O 2 KÀ and H 2 O 2 in regulating autophagy are unknown. In this study, autophagy was induced by starvation, mitochondrial electron transport inhibitors, and exogenous H 2 O 2 . We found that O 2 KÀ was selectively induced by starvation of glucose, L-glutamine, pyruvate, and serum (GP) whereas starvation of amino acids and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
488
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 690 publications
(516 citation statements)
references
References 32 publications
26
488
0
2
Order By: Relevance
“…Therefore, inhibition of prosurvival members of the Bcl-2 family by BH3 mimetics, especially by pan-Bcl-2 inhibitors, might also hamper the antioxidative capacity of cells. Given the fact that oxidative stress is also known to stimulate autophagy in several experimental paradigms (53,54), it is presumably involved in the prominent induction of gossypol-dependent autophagy observed in our experiments. Indeed, (−)-gossypol was previously shown to be a potent inductor of oxidative stress in colorectal cancer cells (22).…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, inhibition of prosurvival members of the Bcl-2 family by BH3 mimetics, especially by pan-Bcl-2 inhibitors, might also hamper the antioxidative capacity of cells. Given the fact that oxidative stress is also known to stimulate autophagy in several experimental paradigms (53,54), it is presumably involved in the prominent induction of gossypol-dependent autophagy observed in our experiments. Indeed, (−)-gossypol was previously shown to be a potent inductor of oxidative stress in colorectal cancer cells (22).…”
Section: Discussionmentioning
confidence: 80%
“…37 Briefly, trypan blue is excluded from live cells but penetrates dead cells giving a red fluorescent signal that can be quantified by flow cytometry.…”
Section: Measurement Of Cell Death By Flow Cytometrymentioning
confidence: 99%
“…•O2 -is the major ROS regulating autophagy (Chen et al, 2009). Recent studies provide strong evidences for the involvement of mitochondrially-generated ROS production in the induction of autophagy (Chen & Gibson, 2008;Chen et al, 2009).…”
Section: Oxidative Stress and Autophagymentioning
confidence: 99%
“…Recent studies provide strong evidences for the involvement of mitochondrially-generated ROS production in the induction of autophagy (Chen & Gibson, 2008;Chen et al, 2009). Recently, it has been demonstrated that targeting mETC complex I by rotenone, induces autophagic cell death through a ROS-mediated mechanism (Chen et al, 2007).…”
Section: Oxidative Stress and Autophagymentioning
confidence: 99%